2011
DOI: 10.1002/jor.21551
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiogenesis after muscle derived stem cell transplantation in injured medial collateral ligament

Abstract: We performed this study to investigate the therapeutic role of vascular endothelial growth factor (VEGF) in medial collateral ligament (MCL) healing. Murine muscle derived stem cells (MDSCs) obtained via the preplate technique were retrovirally transduced to express: (1) VEGF and nLacZ (MDSC-VEGF), (2) soluble fms-like tyrosine kinase-1 (sFLT1, a VEGF-specific antagonist) and nLacZ (MDSC-sFLT1), and (3) nLacZ (MDSC-nLacZ). After transecting the MCL of immunodeficient rats, 5 Â 10 5 cells of each of the transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Type II collagenase (Shanghai Yuanju Bio-Tech Co., Ltd., Shanghai, China) was used for enzymatic digestion to achieve a single-cell suspension from the penile corpora cavernosa tissue. Then, density gradient centrifugation and the preplate technique based on differential adhesion were used, and adherent cells preplate 1 [PP1] were acquired, followed by repeated preplating procedures, until preplate 6 (PP6) cells were acquired Nishimori et al 2012;Nolazco et al 2008), then we confirmed that the PP6 cells were primarily composed of MDSCs.…”
Section: Ethics Statementmentioning
confidence: 76%
“…Type II collagenase (Shanghai Yuanju Bio-Tech Co., Ltd., Shanghai, China) was used for enzymatic digestion to achieve a single-cell suspension from the penile corpora cavernosa tissue. Then, density gradient centrifugation and the preplate technique based on differential adhesion were used, and adherent cells preplate 1 [PP1] were acquired, followed by repeated preplating procedures, until preplate 6 (PP6) cells were acquired Nishimori et al 2012;Nolazco et al 2008), then we confirmed that the PP6 cells were primarily composed of MDSCs.…”
Section: Ethics Statementmentioning
confidence: 76%
“…Other progenitors such as muscle-resident stem cells, known as satellite cells (SCs), are capable of producing a number of angiogenic growth factors. SC transplantation in experimentally injured mouse medial collateral ligament was reported to have accelerated angiogenesis and increased capillary density [8]. Moreover, in the coculture of rat SCs and microvascular fragments, the index of angiogenesis is greater than that of single culture alone [9].…”
Section: Introductionmentioning
confidence: 99%
“…The stimulatory effect of the stem cell-derived CM on endothelial tube-like formation in vitro and arteriolar development in vivo confirmed the importance of paracrine signaling. It has been reported that a number of angiogenic inducers, including FGF, VEGF, IGF, and HGF, are produced by SCs [8]. Also, selected members of metalloproteases and extracellular matrix-degrading enzymes are secreted by human muscle SCs, which may participate in remodeling and in myogenesis [41].…”
mentioning
confidence: 99%
“…Load was applied along the longitudinal axis of the MCL, 100 N load cell was used. A pre-load of 0.1 N was applied to the ligament and the MCL was preconditioned (cyclically loaded to approximately 1 % strain for 10 cycles).After preconditioning, each femur-MCL-tibia complex was stretched at a cross-head speed of 0.25 mm/s until gross failure of the MCL occurred [17]. The load/ displacement readings were taken from the material testing machine output.…”
Section: Biomechanical Testingmentioning
confidence: 99%